Labor judicial mediation from the experience of CEJUSC-JT/Olinda: a case study (Research, Society and Development, 2020)
Part of a broader investigation, this research aimed to analyze the practice of labor mediation from the perspective of mediators and the institutional experience developed in the case-unit, the Judicial Center for Consensual Methods of Dispute Resolution (CEJUSC-JT/Olinda). At the secondary level, the aim was to explore the experience of the Center, highlighting the determining factors of performance, as well as the challenges faced in this practice. In this attempt, the triangulation of methods (documentary, case study and Grounded theory) was adopted as a methodological strategy, with an essentially qualitative design, followed by content analysis. The immersion confirmed the success of the model, highlighting the repercussions of initiatives by the CEJUSC-JT/Olinda administration and its team, especially mediators. In fact, the substantive theories formulated led to the identification of success factors, such as the preparation of the environment and the people involved in mediation procedures. The Center's practices differ on the periphery of the legal (mandatory) rite through its policies and actions. Among these policies, the self-care policy stands out, aimed at people involved in the Center's activities, mediators and support staff. With regard to structural challenges, the parties' resistance to the experiences of mediation and conciliation stands out, the bellicose spirit present in some relationships and the very limitations of the practice in cases of conflicts involving existential damages. These results led to the realization of the need to proceed with the screening of conflicts, aiming at more efficient and effective treatment.